Discovery of Salamandra atra aurorae (Trevisan, 1982) on the Altopiano di Vezzena, Trentino (Northeastern Italy) - Wouter Beukema; Peter Brakels (Acta Herpetologica, 2008)
Aurora’s Alpine Salamander is a limited distributed subspecies endemic to the Altopiano di Asiago, Veneto. In the current paper the occurrence of Salamandra atra aurorae is described for the Altopiano di Vezzena, Trentino. The aim of this paper is to review the distribution as well as to comment on the conservational status of the subspecies in Trentino.